Development of Patchwork Craft Industry Engineering on Sofa Cushions - Juliana, Netty (International Journal of Scientific Research and Management (IJSRM), 2024)
The development of patchwork craft engineering on sofa cushions is a creative activity of students in Medan. The development of sofa cushion crafts uses an explosive qualitative application, namely creating a new design that has never been designed by someone. The purpose of this activity is to increase the creativity and imagination of the younger generation by producing innovative, creative works that have functional value for human life. The concept of developing patchwork sofa cushion crafts starts fro: studying the theory of craft art, literature studies, designing concept maps, shape sketches, designing motifs, the process of making sofa cushions, and presentation of craft results. So this creative activity can increase knowledge and skills in the field of craft art, especially household linen. Thus, the younger generation is expected to be able to become entrepreneurs and be ready to compete in the business world professionally and independently.